Property of a A.P.

Asked by shashwatpns | 14th Mar, 2011, 06:42: PM

Expert Answer:

Dear student,

Since pth term of an AP is q and qth term is p

Therefore, a + (p – 1)d = q                    (i)

and a + (q – 1)d = p                             (ii)  

 Subtracting equation (ii) from equation (i), we get,

(p – 1)d – (q – 1)d = q – p 

d = -1
Substituting the value of d in (1), we get
a = p + q - 1
 
Now, (p+q)th term will be given by

a + (p+q-1)d = p + q - 1 + (p + q - 1)(-1) = 0

 We hope that clarifies your query.

Regards,

Team

TopperLearning 

 

Since pth term of an AP is q and qth term is p
          Therefore, a + (p – 1)d = q                    (i)
          and a + (q – 1)d = p                             (ii)  
          Subtracting equation (ii) from equation (i), we get,
          (p – 1)d – (q – 1)d = q – p 
         

Answered by  | 14th Mar, 2011, 08:28: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.